Rise in temperature causes decreased fitness and higher extinction risks in endemic frogs at high altitude forested wetlands in northern Pakistan. (January 2021) - Saeed, Muhammad; Rais, Muhammad; Gray, Russell J.; Ahmed, Waseem; Akram, Ayesha; Gill, Sumbul; Fareed, Ghulam
Abstract: The larvae of some amphibian species grow and develop more slowly at lower temperature and attain larger body size at the end of metamorphosis, but this is not true for all amphibians. We have for the first time provided empirical data by using a combination of field and lab-based studies with a robust sample size (360 adults, 1000 tadpoles) for Hazara Torrent Frog ( Allopaa hazarensis ) and Murree Hills Frog ( Nanorana vicina ). In this study, we examined how tadpoles responded to different temperatures through metamorphosis, body size, developmental complications or deformities, fitness and survival. We found that the tadpoles of A. hazarensis and N. vicina showed the same response to elevated temperatures under laboratory conditions including faster metamorphosis, reduction in the body size, more frequent developmental complications or deformities such as edema and tail kinks, lower fitness and higher mortality at elevated temperatures (>26 °C). The comparison of thermal sensitivity between the two species showed that N. vicina was more sensitive to higher temperatures. Pakistan has been experiencing changes in climatic patterns, and the ecosystems in northern Pakistan are losing biodiversity due to increasing temperature, frequency of drought and intensity of floods. It is feared that these frogs may experience local extinction in future. Our findings contribute to filling the information gap regarding impacts of temperature increase on biodiversity of high altitude forested montane ecosystems and is an important contribution to future studies associating biodiversity and climate change. Highlights: The study provides empirical data by using combination of field and lab-based studies for Hazara Torrent Frog ( Allopaa hazarensis ) and Murree Hills Frog ( Nanorana vicina ). The tadpoles of both species showed the same response to elevated temperatures under laboratory conditions. Faster metamorphosis, reduction in the body size, lower fitness and higher mortality were observed in tadpoles at elevated temperatures (> 26 °C).